Overcoming Obstacles: Strategic Approaches of MSME Entrepreneurs in North Bekasi - Muhammad Richo Rianto; Suryawan, Ian Nurpatria (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
This research aims to study the influence of strategic marketing, social media, and price on purchasing decisions mediated by purchasing interest. It also focuses on identifying the performance of MSMEs in Bekasi - West Java, which is an area supporting the business. This research uses a quantitative research design with 381 MSME respondents. The analysis unit is 182 MSME respondents assisted by the North Bekasi subdistrict using the Isaac & Michael approach. This research found that strategic marketing, social media, and price did not directly influence purchasing decisions. Meanwhile, buying interest influences purchasing decisions strategic marketing and social media influence purchasing decisions through purchasing interest. Meanwhile, the influence of price on purchasing decisions through purchasing interest is not proven. This research contributes to focusing on a new research model framework that has never been researched.